A decision support tool for a hospital emergency service based on quality of care measurement parameters - Pizán Toscano, Lupe Nerida (2018)
Decision making in the emergency area, given its implication of caring for patients at risk, is extremely sensitive. An inappropriate decision canmake the difference between life and death. The system must respond quickly, efficiently and effectively, and the medical human factor plays the leading role. It can be concluded then that the adequate distribution of the human potential available at the time of emergency is decisive in providing adequate care to the patient. In this work, a model is presented that estimates the appropriate configurations ofmedical equipment in the emergency area, based on parameters measured quantitatively by simulation, which are used to estimate the quality ofthe attention. These parameters support each of the response requirements. There are parameters based on the control of response time, toensure speed of care according to the patient's urgency. In addition, there are other parameters that control whether the patient was treated by the medical team.necessary, according to its urgency, at the appropriate time, and at all times in which, within the department, the patient needed a medical team for their care. The doctor-patient relationship was modeled from both aspects of the doctor and the patients. The patients were modeled according to their urgency, considering four types of patients. The work of the medical staff was modeled taking into account characteristic aspects of medical work, such as their teamwork, the parallelism in patient care of the various medical teams, the work hierarchy within the formation of the teams, and the possibility that the most experienced doctor be part of all medical teams where his participation is necessary. This tool can be used to support decision-making related to the scheduling of medical personnel in the emergency area of ​​a hospital, and has been validated with statistical data from two hospitals, the Antonio Pedro hospital (Niteriói-Brazil) and the Cayetano Heredia Hospital (Lima-Peru).